2021
DOI: 10.1021/acs.est.0c05493
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Fluorescence Measurements of Organic Matter and Bacteria Released in Sea Spray Aerosols

Abstract: Biological aerosols, typically identified through their fluorescence properties, strongly influence clouds and climate. Sea spray aerosol (SSA) particles are a major source of biological aerosols, but detection in the atmosphere is challenging due to potential interference from other sources. Here, the fluorescence signature of isolated SSA, produced using laboratory-based aerosol generation methods, was analyzed and compared with two commonly used fluorescence techniques: excitation–emission matrix spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
(102 reference statements)
6
13
0
Order By: Relevance
“…As a result, high wind speeds resulted in an increase in the number concentrations of bioaerosols as wind-driven transportation of TEP and bacteria from the sea surface to the atmosphere occurred efficiently. Our interpretation is consistent with Santander et al (2021), where the dominance of bacteria in fluorescent sea spray aerosols was confirmed with laboratory-generated aerosol particles and seawater.…”
Section: Association Of Marine Biota To the Formation Of Bioaerosols In The Atmospheresupporting
confidence: 90%
See 2 more Smart Citations
“…As a result, high wind speeds resulted in an increase in the number concentrations of bioaerosols as wind-driven transportation of TEP and bacteria from the sea surface to the atmosphere occurred efficiently. Our interpretation is consistent with Santander et al (2021), where the dominance of bacteria in fluorescent sea spray aerosols was confirmed with laboratory-generated aerosol particles and seawater.…”
Section: Association Of Marine Biota To the Formation Of Bioaerosols In The Atmospheresupporting
confidence: 90%
“…A previous study characterizing fluorescence patterns of a variety of bioaerosols (bacteria, fungi, spore, and pollen) using laboratory experiments showed that Type A particles originated from bacterial and fungi species (Hernandez et al, 2016). Similar results were found with marine bacteria (Santander et al, 2021). Therefore, we infer that bacteria (and fungi, if present) at the sea surface were transported into the atmosphere by wind and were detected as fluorescent particles in the atmosphere.…”
Section: Temporal Variation and Types Of Fluorescent Aerosol Particlessupporting
confidence: 82%
See 1 more Smart Citation
“…One of the major challenges in understanding the dynamics of primary sea spray production is the role of biogenic organic matter (OM) from the surface ocean. A chemoselective transfer of OM from the ocean to the atmosphere is often observed, meaning that some organic compounds are transported to the atmosphere to a larger extent than others (Quinn et al, 2015;Miyazaki et al, 2018;Santander et al, 2021). Here, we have shown that OM have an effect on aerosol particle production rates, which in turn can influence cloud properties, and may therefore be important for the changing climate.…”
Section: Implications and Conclusionmentioning
confidence: 50%
“…For example, Miyazaki et al (2018) showed a consistent enrichment in humic fluorescence with respect to protein fluorescence when comparing SSAs to their respective source water (123-410%). Santander et al (2021) also observed that during the degradation of a simulated phytoplankton bloom, increases in protein fluorescence of bulk seawater were not reflected in an increment of protein-like fluorescence in SSA aerosols, whereas humic fluorescence presented coupled increases in both bulk seawater and SSAs. The changes in dissolved organic matter fluorescence observed during our experiments suggest that not only phytoplankton production but also microbial processing of freshly released DOM may affect aerosol production.…”
Section: Discussion: Linking Ocean-atmosphere Variablesmentioning
confidence: 83%